Perspektif Kriminologi terhadap Kekerasan Anak: Sebuah Analisis Empiris dan Yuridis - Dagani, Gamlan (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2024)
Children are the nation's next generation who need protection from various forms of violence. Despite the enactment of laws on the elimination of domestic violence and child protection, the behavior of violence against children still persists. This paper examines the legal issue of the criminological perspective on child abuse in Abeli District, Kendari City. To address this legal issue, an empirical juridical legal research method is used with a legal sociology approach supported by a statutory approach. This approach is considered appropriate as it will outline data on cases of child abuse in Abeli District and analyze this data to obtain legal insights into how criminology views various forms of child abuse. The research results show that from 2017 to 2020 in Abeli District, Kendari City, there were 57 cases of child abuse. Additionally, child abuse is proven to be a form of criminal act where the perpetrators can be held criminally accountable through both general and special criminal penalties.